Na pochybách. Pascal a Descartes - Gachonová, Kateřina (Filosoﬁcký časopis)
The opposition between the climactic thought of René Descartes and that of Blaise Pascal, although not very explicitly expressed at the time, is considered to be some kind of dispute between “reason and the heart.” An attempt at the relativization of these compartmentalizing poles brings the author of the study to a starting point that is common to Descartes’ Meditations on First Philosophy and Pascal’s Pensées (Thoughts): the act of skepticism and radical doubt. Despite the differences in their skeptical pathways and their goals, the roots of the “systems” of thought of both philosophers grow from this act. The paper attempts to outline how the role of doubt can shape the problem of human knowledge, both on a general level and on the level of the highest, concrete knowledge of Divine Existence.